Reversible Copper Sulfide Conversion in Nonflammable Trimethyl Phosphate Electrolytes for Safe Sodium‐Ion Batteries. Issue 8 (29th June 2021) - Li, Huihua; Zhang, Huang; Diemant, Thomas; Jürgen Behm, R.; Geiger, Dorin; Kaiser, Ute; Varzi, Alberto; Passerini, Stefano
Abstract : Rechargeable sodium‐ion batteries are considered promising candidates for low‐cost and large‐scale energy storage systems. However, the limited energy density, cyclability, and safety issues remain challenges for practical applications. Herein, investigation of the Cu1.8 S/C composite material as the negative electrode active (conversion) material in combination with a concentrated electrolyte composed of a 3.3 m solution of sodium bis(fluorosulfonyl)imide (NaFSI) in trymethyl phosphate and fluoroethylene carbonate (FEC) as the additive is reported on. Such a combination enables the stable cycling of the conversion‐type Cu1.8 S/C electrode material for hundreds of cycles with high capacity (380 mAh g −1 ). Both the salt (NaFSI) and the additive (FEC) contribute to the formation of a stable NaF‐rich solid electrolyte interphase (SEI) on the anode surface. A full cell using the Na3 V2 (PO4 )3 /C cathode also demonstrates stable cycling performance for 200 cycles with a promising Coulombic efficiency (CE) (99.3%). These findings open new opportunities for the development of safer rechargeable sodium‐ion batteries. Abstract : The reversible conversion of copper‐sulfide material is first investigated in a nonflammable phosphate‐based electrolyte for sodium‐ion batteries. The Cu1.8 S/C anode has a promising electrochemical performance with high reversible capacity and rate performance. Full Na‐ion cells featuring Na3 V2 (PO4 )3 /C as the positive electrode show excellent cycling stability. The excellent electrochemical performance is enabled by the NaF‐rich solid electrolyte interphase derived from both the salt and the fluoroethylene carbonate additive.